2014
DOI: 10.1063/1.4880157
|View full text |Cite
|
Sign up to set email alerts
|

Identification of oxygen defects in CdTe revisited: First-principles study

Abstract: Native defects and oxygen and hydrogen-related defect complexes in CdTe: Density functional calculations J. Appl. Phys.By using first-principles calculations, several SO 2 complexes in CdTe were studied. Based on experimental observation, SO 2 complexes have been recently proposed by Lavrov et al. [Phys. Rev. B. 84, 233201 (2011)] to be the cause of the observed IR absorption peaks at 1096.8 and 1108.4 cm À1 in O-doped CdTe. Chen et al. [Phys. Rev. Lett. 96, 035508 (2006)] were originally proposed that the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Therefore, (O i ) is an electrically neutral defect and does not introduce any electronic level in the band gap of CdTe. Its formation energy is calculated to be 1.57 eV in the Te-rich limit and 2.27 eV in the Cd-rich limit, in agreement with recent DFT calculations [77].…”
Section: Interstitial Oxygen (O I )supporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, (O i ) is an electrically neutral defect and does not introduce any electronic level in the band gap of CdTe. Its formation energy is calculated to be 1.57 eV in the Te-rich limit and 2.27 eV in the Cd-rich limit, in agreement with recent DFT calculations [77].…”
Section: Interstitial Oxygen (O I )supporting
confidence: 87%
“…This complex was initially pointed out as responsible for the local vibrational modes (LVMs) observed by Chen et al [78] via infrared spectroscopy. However, this assignment was later discarded by DFT calculations, which showed that the vibrational frequencies in the (O Te -V Cd ) complex are significantly lower than the two modes observed experimentally [25,77]. Our results indicate that this complex has a high formation energy, higher than (O Te ), (O Te -Te Cd ), and (O i ) in both Te-rich and Cd-rich conditions.…”
Section: E (O Te -V CD ) Complexmentioning
confidence: 62%